Biology of COVID-19 and related viruses: Epidemiology, signs, symptoms, diagnosis, and treatment. Issue 3 (October 2021) - Kaye, Alan D.; Cornett, Elyse M.; Brondeel, Kimberley C.; Lerner, Zachary I.; Knight, Haley E.; Erwin, Abigail; Charipova, Karina; Gress, Kyle L.; Urits, Ivan; Urman, Richard D.; Fox, Charles J.; Kevil, Christopher G.
Abstract : Coronaviruses belong to the family Coronaviridae order Nidovirales and are known causes of respiratory and intestinal disease in various mammalian and avian species. Species of coronaviruses known to infect humans are referred to as human coronaviruses (HCoVs). While traditionally, HCoVs have been a significant cause of the common cold, more recently, emergent viruses, including severe acute respiratory syndrome coronavirus (SARS-CoV-2) has caused a global pandemic. Here, we discuss coronavirus disease (COVID-19) biology, pathology, epidemiology, signs and symptoms, diagnosis, treatment, and recent clinical trials involving promising treatments.